Non-Gynecologic and Gynecologic Laparoscopic Surgery During Pregnancy - Yıldırım, Yusuf; Töz, Emrah; Pilancı, Barış; Aykas, Ahmet; Erkan, Nazif (Gynecology Obstetrics & Reproductive Medicine, 2007)
With the popularity of minimally invasive procedures in the last two decades, laparoscopy has been performed for gynecologic and non-gynecologic conditions during pregnancy. In spite of the fact that laparoscopic approach provides some advantages such as less post operative discomfort; many potantial risks including uterine and fetal injury, decreased uterine blood flow due to increased intraabdominal pressure and carbon dioxide absorption can take place during laparoscopy. This review evaluates the literature for laparoscopic surgery during pregnancy.